A thematic review on therapeutic toys and games for the elderly with Alzheimer’s disease - You, Donggui; Ramli, Saiful Hasley; Ibrahim, Rahimah; Romli, Muhammad Hibatullah (Taylor and Francis, 2024)
Purpose: Alzheimer’s disease (AD) is a common and devastating neurological ailment that affects millions of the elderly worldwide. Therapeutic toys and games have emerged as potential non-pharmacological interventions for AD. However, despite a growing number of documents on the subject, research on the future direction of therapeutic toys and games for AD remains scarce. To address this gap, this study aims to (1) map the future trends of therapeutic toys and games for AD and (2) identify the categories and design characteristics. Materials and methods: Using a thematic review framework, a systematic literature search was conducted in two electronic databases (Scopus and WoS) using established criteria. Thematic analysis was done using ATLAS.ti 23 to identify prominent themes, patterns and trends. Results: A total of 180 documents were found. Twenty-five articles met the inclusion criteria. A thematic review of these 25 articles identified 13 initial codes, which were been clustered into four themes: detection and evaluation; intervention; toy/game category; and design characteristics. The word “Cognitive” appears most frequently in documents according to word cloud. Conclusions: Therapeutic toys and games are used to detect and as an intervention for AD. Most of the current studies focused on specific cognitive functions. More research is needed about play therapy for neuropsychiatric symptoms. This thematic review also proposed a conceptual framework for designing toys and games tailored to the needs of the elderly with AD, offering valuable insights to future researchers focusing on this domain.